2022
DOI: 10.1002/advs.202104640
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1 Modulation Mediates Neuroprotective Effects of Statins

Abstract: The ligand‐sensing transcription factor Nurr1 emerges as a promising therapeutic target for neurodegenerative pathologies but Nurr1 ligands for functional studies and therapeutic validation are lacking. Here pronounced Nurr1 modulation by statins for which clinically relevant neuroprotective effects are demonstrated, is reported. Several statins directly affect Nurr1 activity in cellular and cell‐free settings with low micromolar to sub‐micromolar potencies. Simvastatin as example exhibits anti‐inflammatory ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 74 publications
1
39
0
5
Order By: Relevance
“…Compared to previous screening campaigns of the same chemically diverse fragment library on nuclear receptors [20–22] and enzymes, [23] the hit‐rate on NOR‐1 was low. This aligns with the fact that almost no NOR‐1 modulators have been reported to date and suggests that NOR‐1 is particularly restrictive in terms of ligand binding.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared to previous screening campaigns of the same chemically diverse fragment library on nuclear receptors [20–22] and enzymes, [23] the hit‐rate on NOR‐1 was low. This aligns with the fact that almost no NOR‐1 modulators have been reported to date and suggests that NOR‐1 is particularly restrictive in terms of ligand binding.…”
Section: Resultsmentioning
confidence: 71%
“…The commercially available fragment screening library (core set of the Prestwick drug fragments library) comprised 480 compounds with favorable fragment properties (Figure 1a) and offered high structural diversity as illustrated by low average pairwise Jaccard-Tanimoto similarity computed on Morgan fingerprints [16] (median 0.13; Figure 1b) and by a total of 77 unique Murcko scaffolds. [17] Importantly, this library has already yielded valuable ligands for other nuclear receptors including TLX, [18][19][20] Nurr1 [21] and HNF4α. [22] In the initial screening, the library was tested for NOR-1 modulation in the cellular assay at 100 μM in two biologically independent repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid reporter gene assays . Hybrid reporter gene assays were performed in transiently transfected HEK293T cells (German Collection of Microorganisms and Cell Culture GmbH, DSMZ), as described previously [ 36 ], using the hybrid receptor plasmids pFA-CMV-hRARα-LBD [ 37 ], pFA-CMV-hPPARα-LBD [ 38 ], pFA-CMV-hPPARγ-LBD [ 38 ], pFA-CMV-hPPARδ-LBD [ 38 ], pFA-CMV-hVDR-LBD [ 39 ], pFA-CMV-hLXRα-LBD [ 40 ], pFA-CMV-hFXR-LBD [ 41 ], and pFA-CMV-hRXRα-LBD [ 42 ]. pFR-Luc (Stratagene, La Jolla, CA, USA) served as reporter, and pRL-SV40 (Promega, Madison, WI, USA) was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…NR4A monomers bind to the NGFI-B response sequence (NBRE) with the extended motif AAAGGTCA. , Homodimers recognize the so-called Nur response element (NurRE) comprising two half-sites as everted repeat ( TGATATTT ­ACCTCC AAATGCCA ), which was first discovered in the promoter region of the proopiomelanocortin gene. , NR4A heterodimers with RXR bind to the DR5 sequence GGTTCA CCGAA AGGTCA , ,, like other RXR heterodimers that recognize response elements comprising a direct repeat. HTRF-based studies have shown that the oligomerization equilibria of Nurr1 are also sensitive to regulation by ligands and that homo- and heterodimerization can be differentially modulated by ligands. ,,, …”
Section: Structure and Function Of Nurr1mentioning
confidence: 99%
“…A drug fragment screening for Nurr1 modulators has yielded 3-(4-fluorophenyl)­indole ( 11 ) as another fragment-like Nurr1 agonist (EC 50 7.7 μM). 11 is contained as a substructure in the approved drug fluvastatin ( 12 ) which was found to activate Nurr1, as well (EC 50 1.9 μM) . Moreover, other representatives of the statin drug class including pitavastatin ( 13 , EC 50 0.12 μM) and simvastatin ( 14 , EC 50 5.1 μM) exhibited Nurr1 agonism .…”
Section: Nurr1 Ligandsmentioning
confidence: 99%